Local environmental sustainability - Theobald, Kate; Buckingham, Susan, 1953-; ScienceDirect eBooks (Boca Raton, Fla. : CRC ; Cambridge : Woodhead, 2003)
The importance of local programmes in driving sustainable development has been enshrined in Local Agenda 21, arguably the most influential output of the 1992 Rio 'Earth' Summit. Its importance was reiterated by the Johannesburg Summit in 2002. Local environmental sustainability sets the context for local environmental sustainability and, in particular, considers how local government can promote sustainable development by building partnerships with different groups and organisations in the local community. Using case studies, individual chapters focus on different types of regional and local ini.
Building alliances for local environmental sustainability / S. Buckingham, K. Theobald -- Skeletal frameworks / Elizabeth Wilson -- Making the wrecker seem not all malevolent / P. Pinch -- Local Agenda 21 and the shift to 'soft governance" / B. Evans, K. Theobald -- Combating social exclusion / M. Clark, S. Cox -- Retailing and sustainability / P. Garside, A. Hughes, K. Lynch -- Waste minimisation strategies / S. Barr -- Trading places / T.J. Aldridge, A. Patterson, J. Tooke -- Allotments and community gardens / S. Buckingham -- Local economies, trade and global sustainability / P.E. Perkins -- Inequality and community / A. Blowers.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Environmental policy; Community development; Sustainable development; Environmental policy -- Citizen participation; NATURE -- Natural Resources; BUSINESS & ECONOMICS -- Environmental Economics; BUSINESS & ECONOMICS -- Green Business; Community development; Environmental policy; Environmental policy -- Citizen participation; Sustainable development; Electronic books